DeepBrain: Experimental Evaluation of Cloud-Based Computation Offloading and Edge Computing in the Internet-of-Drones for Deep Learning Applications - Koubaa, Anis (2020)
This article belongs to the Special Issue Time-Sensitive Networks for Unmanned Aircraft Systems